Оптимізація довжини кабель-троса при керуванні рухом прив’язного телекерованого підводного апарата - Блінцов, Олександр Володимирович (НТУ "ХПІ", 2016)
На основі аналізу отриманої автором раніше інверсної математичної моделі квазістаціонарного руху кабель-троса (КТ) підводного комплексу з гнучкими зв’язками встановлено, що застосування коефіцієнтів подібності інверсної моделі КТ дає змогу виразити оптимальну за критерієм мінімізації сили натягу довжину випущеної частини КТ в залежності від масштабованої горизонтальної координати його ходового кінця. Синтезовано аналітичну залежність, яка дає змогу розраховувати оптимальну за критерієм мінімізації сили натягу довжину кабель-троса при керуванні прив’язним телекерованим підводним апаратом.

A wide range of underwater operations is performed with the use ofunderwater complexes with flexible tethers (UCFT), which include surface vessels, umbilical cables (UC) and remotely operated underwater vehicles (ROV). The UC has a major disturbing impact on the ROV. Reducing this impact by the UC released part length optimization is a pressing scientific problem. The UC quasi-stationary motion direct and inverse mathematical models are considered. The UC optimum length is typically determined by an iterative search using the UC inverse model. The equations of the similarity coefficients, which make up the UC inverse model are analyzed. It is found that their application allows expressing the optimum, in terms of tension force minimization, UC released part length, based on the scaled horizontal coordinate of its running end. By approximation and by scaling the UC optimumlength iterative search results, the analytical dependence that allows calculating the optimum, in terms of tension force steady-state component minimization, UC length in the ROV control is synthesized. The dependence is implemented by simple computational procedures and can be used in the development of UCFT automatic control systems.
Umbilical cable length optimization at tethered remotely operated vehicle motion control
Keywords: підводний комплекс; кабель-трос; оптимізація довжини; прив’язний підводний апарат; керування; underwater complex; umbilical cable length optimization; tethered underwater vehicle control